1998
DOI: 10.1038/sj.leu.2401060
|View full text |Cite
|
Sign up to set email alerts
|

Cellular resistance mechanisms with impact on the therapy of multiple myeloma

Abstract: Multiple myeloma (MM) is characterized by bone marrow infiltration with abnormal plasma cells which synthesize monoclonal immunoglobulins (Ig) or Ig fragments. Regularly, MM cells exhibit a high intrinsic resistance to available chemotherapeutic strategies. A number of cellular alterations including the cellular membrane, such as mutations of the glucocorticoid receptor or expression of membrane transport proteins, detoxification mechanisms and altered expression of topoisomerases, have been described. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Obviously, MDR 1 is only one of several mechanisms through which myeloma patients may become refractory to chemotherapy (Gieseler & Nussler, 1998;Raaijmakers et al, 1998;Sonneveld, 1999). The question remains whether a benefit by MDR 1 reversal may be expected early during the disease, when the frequency of MDR 1 and other resistance pathways may still be low, as opposed to highly refractory patients who have no other treatment options left (Futscher et al, 1996;Pilarski et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, MDR 1 is only one of several mechanisms through which myeloma patients may become refractory to chemotherapy (Gieseler & Nussler, 1998;Raaijmakers et al, 1998;Sonneveld, 1999). The question remains whether a benefit by MDR 1 reversal may be expected early during the disease, when the frequency of MDR 1 and other resistance pathways may still be low, as opposed to highly refractory patients who have no other treatment options left (Futscher et al, 1996;Pilarski et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Searching from the opposite direction, Rosenblum et al (1995) found that melanoma cells (A375‐M) that were made resistant for the IT ZME‐gelonin (also type I), by incubating with the IT, also became resistant for the cytostatics vincristine and doxorubicin. If all findings are taken together, the conclusion may be that (type I) IT resistance is not directly related to P‐gp but to other, currently unknown, mechanisms that are co‐selected with development of resistance (Gieseler and Nubler, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that MDR1 expression is an independent prognostic factor associated with a poor outcome in acute myeloid leukemia, non-HodgkinЈs lymphoma, and acute lymphoblastic leukemia (16). In MM, a careful analysis of the literature shows the existence of disturbing discrepancies in the incidence of MDR1 overexpression, ranging from 0% to 41% of cases (17)(18)(19)(20)(21). Such a variability has been related, at least in part, to technical questions.…”
mentioning
confidence: 99%
“…However, different clones have been employed (18,20). In other reports, functional assays have been used in which either the doxorubicin or the rhodamine 123 efflux were measured (17,22). An additional factor that may contribute to discrepant results is that MDR1 expression is measured on total BM cells and not specifically on PC.…”
mentioning
confidence: 99%
See 1 more Smart Citation